Biochemical Verification of Tobacco-Use as an Inclusion Criterion in Smoking Cessation Trials- Lessons From the Cessation of Smoking Trial in the Emergency Department - Ian Pope MBBS; Chandhini Suresh MPH; Emma Ward PhD; Pippa Belderson PhD; Caitlin Notley PhD (SAGE Publishing, 2023)
INTRODUCTION Biochemical verification of smoking status prior to recruitment into smoking cessation trials is widely used to confirm smoking status, most commonly using exhaled carbon monoxide (CO). There is variation in the level of CO used as a biochemical inclusion criterion, and thus the possibility for people reporting to be current smokers to be incorrectly excluded from trials. METHODS As part of the Cessation of Smoking Trial in the Emergency Department, people attending the Emergency Department (ED) who reported being current daily smokers underwent CO testing to confirm eligibility. Elective semi-structured interviews were undertaken with the researchers who recruited participants. As part of the interviews, researchers were asked their views and experiences with CO testing. RESULTS Of the 1320 participants who reported being current daily smokers and underwent CO testing, 300 (22.7%) blew a CO reading of 7 ppm or less and were excluded from taking part. Possible explanations offered by researchers for participants blowing low CO readings were (1) long wait times in the ED, therefore a long period having elapsed since people had last smoked and (2) patients having reduced smoking for the period before the ED attendance due to ill health. CONCLUSIONS Biochemical verification has the potential to improve internal validity of smoking cessation for inclusion in trials, but at the cost of reduced generalisability through exclusion of participants who would receive the intervention if it were implemented in practice. We would recommend researchers carefully consider whether it is appropriate and necessary to include biochemical verification as an inclusion criterion.